Everolimus with cyclosporine withdrawal or low-exposure cyclosporine in kidney transplantation from Month 3: a multicentre, randomized trial - Budde, Klemens; Zeier, Martin; Sommerer, Claudia (Nephrology, dialysis, transplantation, 2017)
Abstract. Background. Randomized trials have shown that early adoption of everolimus-based immunosuppressive regimens without a calcineurin inhibitor (CNI) imp
Gesehen am 23.08.2018